Experimental Verification of Circulating Current Mitigation Scheme in MMC by Using ISE Technique - Sreedhar Madichetty; Abhijit Dasgupta (Institute of Advanced Engineering and Science, 2014)
The circulating currents of a modular multilevel converter (MMC) is ideally assumed to be the sum of an ac component and dc ac component operating with fundamental frequency. However, as ac current flows through the submodule (SM) capacitors, the capacitor voltages fluctuate with time. Consequently, the circulating current is usually distorted and allows multiple frequency components with the peak value of it is increased compared with the theoretical value. The circulating currents will increase power losses and may threaten the safe operation of the switching devices and module capacitors. This article proposes a MMC with a new controller design to mitigate circulating currents for various modulation indexes for wide ranges in load. This new controller is optimized with upper and lower module voltages as an objective function. The optimum values for controller are obtained by using conventional integral square error technique (ISE). The proposed scheme shows its effectiveness by controlling the circulating currents for various loads. It made strategic conclusions on MMC to make the system more robust in operation and less complexity in design and control. The proposed system is verified by 10 KVA prototypes MMC and results are explored. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5364